A species-specific nucleosomal signature defines a periodic distribution of amino acids in proteins - Luis Quintales; Ignacio Soriano; Enrique Vázquez; Mónica Segurado; Francisco Antequera (Open Biology, 2015)
Nucleosomes are the basic structural units of chromatin. Most of the yeast genome is organized in a pattern of positioned nucleosomes that is stably maintained under a wide range of physiological conditions. In this work, we have searched for sequence determinants associated with positioned nucleosomes in four species of fission and budding yeasts. We show that mononucleosomal DNA follows a highly structured base composition pattern, which differs among species despite the high degree of histone conservation. These nucleosomal signatures are present in transcribed and non-transcribed regions across the genome. In the case of open reading frames, they correctly predict the relative distribution of codons on mononucleosomal DNA, and they also determine a periodicity in the average distribution of amino acids along the proteins. These results establish a direct and species-specific connection between the position of each codon around the histone octamer and protein composition.